(untitled) (ACTA MEDICA PERUANA, 2023)
Objetivo: To determine the correlation between salivary glucose levels with fasting blood glucose, HbA1c, and C-peptide in patients with type 2 diabetes mellitus (T2DM). Materials and methods: This is a cross-sectional study performed at the Centro de Investigación en Diabetes, Obesidad y Nutrición (CIDON) in Lima, Peru, during 2021. Patients were categorized as those with good metabolic control (HbA1c<7 %), and poor metabolic control (HbA1c≥7 %). Baseline fasting blood glucose, as well as blood HbA1c and C-peptide values were measured. Salivary glucose was measured using the glucose oxidase method. Spearman’s correlation was used for determining an association between salivary glucose levels and fasting blood glucose, HbA1c, and C-peptide. Results: One-hundred and forty-two subjects with T2DM participated in the study. Salivary glucose was significantly higher in T2DM subjects with poor metabolic control (p<0.01). A weak positive correlation between salivary glucose and fasting blood glucose (r= 0.23, p= 0.04) and HbA1c (r= 0.26, p= 0.02) was observed in subjects with T2DM and poor metabolic control, and also a non-significant negative correlation (r=-0.08; p= 0.47) with C-peptide. Conclusions: Salivary glucose levels show significant and positive association with fasting blood glucose and HbA1c, but not with C-peptide in persons with T2DM and poor metabolic control. However, there are many factors that should be considered and analyzed in detail aiming to determine its potential use.